Mental distress in treatment seeking young adults (18–25 years) with severe obesity compared with population controls of different body mass index levels: cohort study. (6th January 2017) - Dreber, H.; Reynisdottir, S.; Angelin, B.; Tynelius, P.; Rasmussen, F.; Hemmingsson, E.
Summary: Young adults (18–25) with severe obesity constitute a challenging patient group, and there is limited evidence about their mental health status compared to population controls. Mental distress in treatment seeking young adults with severe obesity ( n = 121, mean body mass index [BMI] = 39.8 kg m −2 ) was compared with matched (1:3 for age, gender and socioeconomic status) population controls of normal weight ( n = 363, mean BMI = 22.4 kg m −2 ), as well as unmatched population controls with class I obesity ( n = 105, mean BMI = 32.1 kg m −2 ) or severe obesity ( n = 41, mean BMI = 39.7 kg m −2 ). Mental distress was measured by the General Health Questionnaire‐12 (GHQ‐12), and we quantified physician‐diagnosed depression, present anxiety and suicide attempts. Poisson regression and linear regression analysis were used for analysing differences in mental distress between groups. Treatment seekers experienced more mental distress than normal weight controls as measured by continuous (adjusted mean: 3.9 vs. 2.2 points, P <0.001) and categorical (cut‐off for mental distress ≥3 points, RR: 1.76, P <0.001) GHQ‐12 scores, depression (RR: 2.18, P < 0.001), anxiety (RR: 1.97, P < 0.001) and suicide attempts (RR: 2.04; P = 0.034). Treatment seekers also experienced more mental distress as measured by continuous GHQ‐12 than controls with class I obesity (adjusted mean: 2.3 points) or severe obesity (adjusted mean: 2.1; both, P < 0.001). Young adult treatment seekers with severe obesity constitute a risk group for mental distress compared to population controls of different BMI levels.